Assessment of Knowledge on Essential Newborn Care among Nurses Working in Maternity Homes of Ahmedabad Municipal Corporation - Zaveri, Niyati H; Bala DV (National Journal of Community Medicine, 2019)
Introduction: Essential newborn is important starting-point for any neonatal program. It is very important that health care service providers have good knowledge about it. This study was con- ducted to assess the knowledge of the nurses about it. The study was conducted to assess the knowledge of the nurses about essen- tial newborn care, working in the maternity homes of Ahmedabad municipal corporation area. Methodology: The study is descriptive type, which was conducted in year2016-17.Knowledge was tested using questionnaire. All the nurses who had training in Essential Newborn care were included and nurses who did not want to be part of the study were ex- cluded. Results: Out of all 94.2% nurses had training in essential newborn care. The Mean score was 13.7 + 3.19.82.8% nurses knew when to initiate breastfeeding,98.3% knew average Indian baby weight.50% of the maternity homes had no staff nurse vacancy. Two of the ma- ternity homes had Caesarean section done.75% of nurses had knowledge about Breastfeeding and 54.4% nurses about Breathing as Component of Essential newborne.58% percent of the nurses knew APGAR score components.64-66% nurses had knowledge about cleans of delivery. Conclusion: The vacancy of nurses was significant. Almost all nurse had training in Essential newborn care, still test mean score was low. The Caesarean section and assisted delivery wasn’t available in all the maternity homes.